PENGARUH BOARD CHARACTERISTIC TERHADAP PENGUNGKAPAN LAPORAN KEBERLANJUTAN - Maria Euginia; Wijaya Triwacananingrum (Ultimaccounting Jurnal Ilmu Akuntansi, 2022)
Abstract – The purpose of this study is to see how characteristics of the board of directors affect the disclosure of sustainability reports. This study collects samples through purposive sampling technique. A total of 135 sample data were taken from companies in Indonesia that were included in the Kompas 100 index, for three consecutive years, which disclosed sustainability reports. The year under study is the latest and closest year, 2018-2020. Disclosure of sustainability reports will use the GRI Sustainability Report Disclosure Index (SRDI) indicator (2018) with a total assessment of 250 indicators, each indicator listed will be given a value of one. The size of the board of directors will be using the natural logarithm of board size. Board gender diversity from both sides will use their respective proportions to the entire board of directors. The STATA program was used in this study because it was considered the most suitable for the research technique. This research resulted in board size having a significant and positive effect on the disclosure of sustainability reports. Board diversity from female on board has an effect but not significantly on the disclosure of sustainability reports. Finally, board diversity from male on board also has an effect but not significantly on the disclosure of sustainability reports. Keywords: Board Characteristic; Sustainability Report Disclosure; Board Size; Board Diversity